التحديات التي تواجه القيادات النسائية السعودية في مؤسسات القطاع العام - العايد، سري إبراهيم (جامعة العلوم الإسلامية العالمية - عمادة البحث العلمي, 2021)
اهتم الباحثون بتمكين المرأة بمنظمات الأعمال، وأهمية دورها جنبا إلى جنب مع الرجل لاسيما في المجتمعات النامية. لذا هدفت هذه الدراسة إلى الكشف عن التحديات التي تواجه القيادات النسائية السعودية في مؤسسـات القطاع العام، وبيان مدى اختلاف هذه التحديات وفقا لخصائصهن الشخصية والوظيفية، وطبقت الدراسة على 83 امرأة تم اختيارهن بطريقة غير عشوائية (ملائمة) بمنطقة الرياض، وبينت النتائج إن أكثر المشكلات الـتي تواجه القيادات النسائية السعودية كانت تدني نظرة القائد الإداري لعمل المرأة، وعدم القناعة والثقة بقرارات المرأة وآرائها، إلى وأشارت النتـائج كذلك إلى عدم وجود اختلاف في التحديات التي تواجه القيادات النسائية في مؤسسات القطاع العام باختلاف خصائصهن الشخصية والوظيفية. ومن أهم التوصيات التي قدمتها الدراسة: العمل على تهيئة الصف الثاني من القيادات النسائية الشابة، وإشراكهن في العملية القيادة من أجل صقل خبراتهن ومهارتهن، والتركيز على التدريب المستمر للقيادات النسائية من أجل تنمية مهارات المرأة القيادية.
The researchers were interested in empowering women in business organizations and their vital role side by side to men, particularly, in the developing societies. So, this study aimed at detecting the challenges that face the Saudi women leaders in the public sector institutions, beside showing the extent of the differences of these challenges according to their occupational and personal characteristics. This studies was applied to 83 women who were chosen by using non-random samples in Riyadh. The results showed that the majority of the problems which the Saudi women leaders face were the degradation perspective of the administrative leader toward the women’s career; in addition to the non-contentment and the non-confidence of the women’s decisions and views. The results also indicated that there is no difference in the challenges that the Saudi women leaders face in the public sector institutions with different personal and functional characteristics. This study presented some significant recommendations such as: - Preparing the second-row of young women leadership and involving them in the leadership process to enhance their experiences and skills. - Focusing on the continuous training for women’s leadership to develop the women’s leadership skills.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- القيادة النسائية السعودية -- القطاع العام -- السعودية